DAKWAH DALAM MENINGKATKAN ETOS KERJA MASYARAKAT DESA BONTO SOMBA KECAMATAN TOMPOBULU KABUPATEN MAROS (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Dakwah or Da’wah (Proselytism of Islam) is moeslem religious activity, in form of acts, words (speech) and efforts (both mentally and spiritually) to enhance and improve knowledge in many aspects of life, especially the true meaning of Islam, and how it should actualize as the way of thinking and daily acts, to invite people and society to a better way according to the Qur’an. Da’wah also aims to form a better life of society to fulfil the concept of “Happiness in this life and life after”. The purposes of this study are to show how Da’wah activity could enhance and improve the work ethic as it’s part to shape character, to promote change to modernizations, how Da’wah Motivate people dan Da’wah’s role to share knowledge and Islamic perspectives. Supporting factor in society that make Da’wah easier for people to accept dan to improve the society’s work ethic was the government policy, the society’s openness, the high spirited society and collaboration between community and organization.